A STYLISTIC ANALYSIS OF DERIVATIONAL MORPHEME ON NARRATIVE TEXTS IN EFL TEXTBOOK - Yusep Nurdiana Putra; Iskhak Said; Rita Apollonia (Journal of English Education Program (JEEP), 2021)
The research reported in this paper centered on the issue of derivational morphemes analysis which uses narrative texts as the object of the study. Out of 15, 6 narrative texts were chosen from EFL Textbook of Senior High School ‘Developing English Competencies’. Afterwards, the writer set two research questions: to investigate the kinds and the dominant affixes of derivational morphemes which are mostly used on Narrative Texts in EFL Textbook. This study employed qualitative strategies by using content analysis as the instrument of gained data. The results for the first question asserted that among three kinds such as prefix, infix and prefix, there were only two kinds derivational morpheme founded on narrative texts in EFL Textbook, both of these derivational morphemes were prefix and suffix. Besides, the infix was not founded on the whole of the texts. Moreover, the results for the second research question revealed that the dominant affixes mostly used on narrative texts in EFL textbooks was the suffix. Finally, it is expected that on narrative texts, suffix was the important rule to compose the text intact. Moreover, the other affixes such prefix and infix were lower than suffix on the whole of the texts. For instance, ‘ly’ and ‘ed’ as affixes that was added and used on narrative text in EFL textbook that was analyzed. In the meantime, in every texts that have been analyzed, most of the affixes, both prefix and suffix changed the part of speech of the root when changed to the new word. It is suggested for further researchers to conduct the research on by using the other texts by covering derivational and inflectional morphemes. Keywords:  stylistic, derivational morphemes, narrative text, EFL Textbook